Aliphatic hydrocarbons in the lichen class Lecanoromycetes and their potential use as chemotaxonomic indicators and biomarkers. (May 2023) - Ikeda, Masashi A.; Nakamura, Hideto; Sawada, Ken
Highlights: Alkene compositions in lichens vary depending more on taxonomy than environment. Long-chain anteiso -alkanes were particularly abundant in genus Cladonia . Fernene and diploptene may be derived from internal bacteria in lichens. Alkenes and long-chain anteiso -alkanes can be used as lichen biomarkers. Abstract: Lichens are found in a wide range of terrestrial habitats and have important roles in terrestrial ecosystems. However, because lichens are easily decomposed and are rarely preserved as fossils, their paleoenvironmental ecology and evolutionary history remain a mystery. We performed lipid analyses on 29 lichen samples belonging to Lecanoromycetes, the largest class of lichens, from several locations in Japan, to determine their potential for use as taxonomic tools and biomarkers. We found that the lichens contained aliphatic hydrocarbons, including n -alkanes, alkenes, and long-chain branched alkanes, fernenes, diploptene, and hop-21-ene. Lichens with a green algal photobiont (photosynthetic symbiotic algae) contained 1, 8-heptadecadiene or 6, 9-heptadecadiene and 8- and 7-heptadecene, whereas lichens with cyanobacteria as a photobiont did not contain the heptadecadienes but did contain octadecene, nonadecene and nonadecadiene. These differences in characteristics could be attributed to phylogenetic differences in the photobionts that comprised the lichens, indicating that the alkene composition could be used for lichen chemotaxonomy. Although additional research is needed to confirm that this signal gets preserved in sedimentary archives, our results suggest a previously unknown origin for the C17 –C19 alkenes in sediments and imply that these components could be used to reconstruct the past composition of lichens.